Development of Scientific Argumentation Test Instruments for Students on the Classification of Living Creatures in Junior High School - Yovita; Sonia, Gina; Vebrianto, Rian; Susanti, Emilia; Berlian, Mery (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2024)
Development of Scientific Argumentation Test Instruments for Students on the Classification of Living Creatures in Junior High School. Encouraging students to think and act like scientists is an important basis of the scientific approach to learning. Both students and scientists need arguments. This study uses a research and development (R&D) approach concerning the ADDIE model. The validation stage has been carried out by experts—linguists, material experts, and media experts—as well as one-on-one trials, small groups, and teacher practice. It can be concluded that the results of the expert validation as a whole.